Indonesian political exiles in the Netherlands after 1965; Postcolonial nationalists in an era of transnationalism - Hill, David T. (UI Scholars Hub, 2022)
This article presents brief life stories of select Indonesians who were forced into exile by the Suharto regime after the 1965 National Tragedy in Indonesia. It focuses on staunch nationalist exiles who were rendered stateless by the self-proclaimed “New Order“ for refusing to accept the overthrow of President Sukarno and declare loyalty to the military regime. Faced with a life in exile, they sought refuge in the former colonial nation of the Netherlands. After exploring a brief history of exile in the bilateral relationship, it explores the choices made by select individuals who moved to the Netherlands from a variety of other locations of initial refuge. It then explores the frameworks of support which bolster the exiles’ sense of identity as Indonesian (trans)nationalists who reside in the Netherlands, before finally locating the experiences of the exiles in the context of their changing engagement with their homeland.